DNA-based artificial molecular signaling system that mimics basic elements of reception and response - Ruizi Peng (Nature Portfolio, 2020)
Cells communicate with the outside world to maintain homeostasis. Here the authors design a synthetic biology DNA-based signalling system AMSsys that responds to the presence of ATP.